How High Quality Rice Shapes Repeat Purchases and Word of Mouth: The Role of Value and Satisfaction - Diana Fajarwati; Holby Boy Martua Manurung; Unggul Kustiawan; Puspita Chairun Nisa (CV. Ulil Albab Corp, 2024)
Organic rice has gained importance due to its health benefits, especially for individuals aged 28 and older who have adopted a healthy diet. Organic rice is known to reduce the risk of diseases like diabetes, cancer, obesity, and brain development disorders. This highlights the significant impact of organic rice quality, encouraging consumers to purchase it without hesitation. This study investigates the influence of Food Quality, Perceived Value, Price Fairness, and Customer Satisfaction on Repurchase Intention and Word of Mouth in the context of offline organic rice sales.A sample of 125 respondents was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationships between variables. The findings reveal that Food Quality positively affects Price Fairness and Customer Satisfaction, while Price Fairness also positively impacts Perceived Value. In turn, Perceived Value enhances Customer Satisfaction, and Customer Satisfaction leads to higher Repurchase Intention and Word of Mouth. Of the eight proposed hypotheses, six were accepted (H1, H3, H4, H6, H7, H8), while two (H2 and H5) were rejected. Future researchers should consider these variables carefully to avoid inconsistent results. In this study, the Revisit Intention variable was adjusted to Repurchase Intention for better alignment with the research context.